2019
DOI: 10.20473/juxta.v10i22019.52-56
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Family Socioeconomic Status and the Delayed Treatment of Retinoblastoma Patients at Dr. Soetomo General Hospital Surabaya

Abstract: Introduction: Retinoblastoma is a cancer with the highest incidence in children and the second type of cancer that most often causes death in children in Indonesia. The level of delay in attending treatment for retinoblastoma patients in Dr. Soetomo General Hospital Surabaya is still high because in general the patients come with an advanced stage, they are already in serious condition or with a poor prognosis. Treatment delay from the patients can be caused by the patients that are not feeling disturbed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The sex distribution in this study was not much different from a global study with 55% males and 45% females 35 . This finding is also in accordance with research conducted in Surabaya (51.5 vs. 48.5%), 13 Bali (54 vs. 46%), 14 Yogyakarta with the overall population of malignancies (57.3 vs. 42.7%), 4 and India (52.9 vs. 47.1%) 15 . This ratio is consistent with the pathogenetics of retinoblastoma that involves a mutation which occurs in the RB1 gene is known to be unrelated to the sex chromosome 1,16 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The sex distribution in this study was not much different from a global study with 55% males and 45% females 35 . This finding is also in accordance with research conducted in Surabaya (51.5 vs. 48.5%), 13 Bali (54 vs. 46%), 14 Yogyakarta with the overall population of malignancies (57.3 vs. 42.7%), 4 and India (52.9 vs. 47.1%) 15 . This ratio is consistent with the pathogenetics of retinoblastoma that involves a mutation which occurs in the RB1 gene is known to be unrelated to the sex chromosome 1,16 …”
Section: Discussionsupporting
confidence: 91%
“…21 Genetic and clinical examinations in children with a history of parents or siblings suffering from retinoblastoma are important to accelerate diagnosis and therapy, and ultimately improve the quality of life of patients with retinoblastoma. 22 The lag time to diagnosis in this study had a median value of 10.5 months (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). A retrospective study in India reported the delay was only 5 months (1-36).…”
Section: Prognostic Factorsmentioning
confidence: 60%
“…Educational level of parents was not statistically not associated with prognosis [16]. However, income level of the family (p<0.03) and the occupation status of the father (p<0.03) were significantly associated with prognosis [16].…”
Section: Indonesiamentioning
confidence: 79%
“…In addition, there was also inadequacy of management including monitoring of treatment response either as a result of poor medical documentation or poor patient follow-up [13,17]. Resorting to alternative medicine or waiting for the condition to get worse even after being advised treatment further contributed to low survival [16]. There was a series where there were no records on the disease classification making it hard to determine which indication and treatment modality were used [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation